Pembelajaran Kosakata Bahasa Arab Melalui Kegiatan Ilqoul Mufradat - Sholeha, Fathma Zahara; Al Baqi, Safiruddin (Institut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2023)
This research aims to provide a detailed and in-depth description of the Ilqoul Mufradat activities in Arabic vocabulary learning at Wali Songo Ngabar Islamic Boarding School. The research method employed is qualitative with a case study approach. Data were obtained through interviews, direct observation, and documentation. The research interview subjects were three language instructors at Wali Songo Ngabar Islamic Boarding School. Meanwhile, observation was conducted concerning the language-related activities of the students. The results of this research reveal that vocabulary instruction through Ilqoul Mufradat activities is conducted through Talfidz (enunciation), Tikrar (repetition), exercises and practice, writing vocabulary in notebooks, using the vocabulary in everyday communication, and evaluation. The activities impact students' abilities to comprehend and employ Arabic vocabulary, along with the challenges encountered in using vocabulary in daily communication activities.